Выбор оптимальных параметров двухступенчатых пластинчатых подогревателей - Арсеньева, Ольга Петровна; Демирский, А. В.; Хавин, Геннадий Львович (НТУ "ХПИ", 2011)
The analytical correlation of optimal permissible pressure drop and intermediate temperature between two plate heat exchangers is obtained. That correlation is met of the minimum of discounted value. The design of two sugar juice heaters before evaporator system is demonstrated high efficiency of this solution.
Keywords: подогреватель; теплоноситель; тепловая нагрузка; теплообменник; сахарный сок